Motivation of tourists visiting agritourism (case study: BuyFresh ByFarm in Singkawang) - Erawatilah, Erawatilah; Dolorosa, Eva; Suharyani, Anita (Agriekonomika, 2025)
Indonesia has abundant potential and resources but has not been developed optimally, one of which is the tourism sector. In efforts to increase tourism potential, agritourism development has become one of the popular strategies, however, there are still few agritourism locations in West Kalimantan that have not developed even though they have great potential to increase tourist visits. Tourists visit a tourist spot motivated by motivation. The purpose of this study was to determine the push factors and pull factors that influence the motivation of tourists to visit BuyFresh ByFarm agritourism. The results showed that the push factors and pull factors that influence the motivation of tourists to visit BuyFresh ByFarm agrotourism are only influenced by push factors, namely the escape variable, and the rest is influenced by other factors outside the factors studied in this study.